The crystal structure of poly[aqua-(μ2-4,4′- bis(imidazolyl)biphenyl-κ2N:N′)-(μ2-3-nitrobenzene-1,2-dicarboxylato-κ2O:O′)]copper (II) hydrate, C26H21N5O8Cu - Li Gui-Lian; Liu Meng-Ni; Du Gao-Jing; Zhang Jin-Yuan (Zeitschrift für Kristallographie - New Crystal Structures)
C26H21N5O8Cu, monoclinic, P21/c (no. 14), a = 17.2262(10) Å, b = 7.3474(3) Å, c = 21.1086(11) Å, β = 111.498(6)°, V = 2485.8(2) Å3, Z = 4, Rgt(F) = 0.0629, wRref(F2) = 0.1433, T = 293(2) K.